Complex optical/UV and X-ray variability in Seyfert 1 galaxy Mrk 509. (6th September 2021) - Kumari, Neeraj; Pal, Main; Naik, Sachindra; Jana, Arghajit; Jaisawal, Gaurava K.; Kushwaha, Pankaj
Abstract: We performed a detailed spectral and timing analysis of a Seyfert 1 galaxy Mrk 509 using data from the Neil Gehrels Swift observatory that spanned over $\sim$ 13 years between 2006 and 2019. To study the variability properties from the optical/UV to X-ray emission, we used a total of 275 pointed observations in this work. The average spectrum over the entire duration exhibits a strong soft X-ray excess above the power law continuum. The soft X-ray excess is well described by two thermal components with temperatures of kT $_{\rm BB1}\sim$ 120 eV and kT $_{\rm BB2}\sim$ 460 eV. The warm thermal component is likely due to the presence of an optically thick and warm Comptonizing plasma in the inner accretion disk. The fractional variability amplitude is found to be decreasing with increasing wavelength, i.e., from the soft X-ray to UV/optical emission. However, the hard X-ray (2–8 keV) emission shows very low variability. The strength of the correlation within the UV and the optical bands (0.95–0.99) is found to be stronger than the correlation between the UV/optical and X-ray bands (0.40–0.53). These results clearly suggest that the emitting regions of the X-ray and UV/optical emission are likely distinct or partly interacting. Having removed the slow variations in the light curves, we find that the lag spectrum is well described by the 4/3 rule for the standard Shakura–Sunyaev accretion disk when we omit X-ray lags. All these results suggest that the real disk is complex, and the UV emission is likely reprocessed in the accretion disk to give X-ray and optical emission.